Pelaksanaan Program Gerakan Pensejahteraan Ekonomi Masyarakat Pesisir dan Dampaknya di Kelurahan Pasie Nan Tigo, Kota Padang - Dewi, Thahira Kemala; Agustar, Asdi; Mahdi, Mahdi (JPPUMA Jurnal Ilmu Pemerintahan dan Sosial Politik Universitas Medan Area, 2019)
This study aims to discover how The Coastal Community Economic Welfare Program (GPEMP) programwas implemented and its impact on the orientation of fishermen's family income-sources in Pasie Nan Tigo Subdistrict, Koto Tangah District, Padang City. The method used in this study is a case study method with key informants as the main data source. Interviews were conducted with key informants and direct observations in the field related to the problems raised in this study.Data analysis through a qualitative approach.The results showed that the GPEMP program had been implemented in accordance with the implementation instructions, except in the GPEMP assistance delivery phase, namely the assistance of developing fish culture with the help of a fixed net package and tilapia cultivation equipment where there were differences in the specifications of the goods delivered with the supposed ones. The GPEMP program has impacts on the orientation of fishermen's family income sources in Pasie Nan Tigo Subistrict, namely: 1) fishermen's family income sources developed to become not only from fishing, but also from other new alternative livelihoods, such as fish cultivation, fish processing diversification, and cattle farming, and 2) fishermen's effectiveness working hours increases as well as involvement of fishermen's wives and children’s involvement in the business.